Prognostic Value of Perineural Invasion on Survival and Recurrence in Oral Squamous Cell Carcinoma - Spoerl, Steffen; Spörl, Silvia; Reil, Stephanie; Gerken, Michael; Ludwig, Nils; Taxis, Juergen; Fischer, René; Ettl, Tobias; Reichert, Torsten E.; Spanier, Gerrit (Diagnostics, 2022)
A diagnosis of perineural invasion (PNI) is widely accepted as an unfavorable prognostic factor in various solid malignancies. Although PNI has been described as a high-risk parameter in oral squamous cell carcinoma (OSCC), its role in the current staging manuals of the American Joint Committee on Cancer (AJCC) is rather subordinate. We analysed the prognostic value of PNI on survival and recurrence in a large, multicenter OSCC cohort and a population-based approach. A total of 493 OSCC patients with primary tumor resection to negative margins and concomitant neck dissection between 2010 and 2017 were enrolled. PNI was evaluated in relation to overall survival (OAS) and recurrence-free survival (RFS) using uni-and multi-variable Cox regression. The median follow-up time was 5.0 years and PNI was diagnosed in 48 patients (9.7%). A patho-histological verification of PNI correlated significantly with a deteriorated OAS in uni-(HR 2.312; 95% CI 2.312–3.493, p = 0.001) and multivariable Cox regression (HR 1.820; 95% CI 1.164–2.847, p = 0.009). Additionally, a diagnosis of PNI correlated with increased cumulative, as well as distant, metastasis 5-year-recurrence rates (p = 0.027 and p = 0.011, respectively). The application of adjuvant radiotherapy (RT) or radiochemotherapy (RCT) in patients with PNI did not alter OAS or RFS in survival analysis when compared to patients without PNI. The results underline the adverse impact of PNI on the survival and recurrence of surgically treated OSCC patients. Based on our findings, we highly recommend an emphasis on PNI in the TNM staging concept.
CRIS-Team Scopus Importer:2022-05-20
Keywords: oral cancer; oral squamous cell carcinoma; perineural invasion; PNI; recurrence; survival